Odpowiedzi

2010-03-09T15:39:28+01:00
A)3b+(b+1)= 3b + b + 1 = 4b + 1
b)5a-(a+1)= 5a - a - 1 = 4a - 1
c)2x-(3-5-x)= 2x - 3 + 5 + x = 3x + 2
d)2a+(3a-2b)+(a+b)= 2a + 3a - 2b + a + b = 6a -b
e)5a-(2-x)+b-2x+5= 5a - 2 + x + b - 2x + 5 = 5a +3 - x
f)7k-(m-2n+k)-(5k-3)+(2k-1)= 7k - m + 2n - k - 5k + 3 + 2k - 1 = 3k -m + 2n +2
g)0,3x-(5+0,7y)-(0,9-0,1x)+(x-0,1)= 0,3x - 5 - 0,7y-0,9+0,1x+x-0,1=1,4x-6-0,7y
h)0,5a+(5-0,8b+2a)-(-b+1)=0,5a+5-0,8b+2a+b-1=2,5a+4+0,2b
i)3/4-(1/4x+1/2)=3/4-1/4x-1/2=1/4-1/4x
j)1/3x+1/9y+(2/3y-4/9x-2/7)=1/3x+1/9y+2/3y-4/9x-2/7=-1/9x+7/9y-2/7
Najlepsza Odpowiedź!
2010-03-09T15:41:20+01:00
A)3b+(b+1)=3b+b+1=4b+1
b)5a-(a+1)=5a-a-1=4a-1
c)2x-(3-5-x)=2x-3+5+x=3x+2
d)2a+(3a-2b)+(a+b)=2a+3a-2b+a+b=6a-b
e)5a-(2-x)+b-2x+5=5a-2+x+b-2x+5=5a+b-x-2
f)7k-(m-2n+k)-(5k-3)+(2k-1)=7k-m+2n-k-5k+3+2k-1=3k-m+2n+2
g)0,3x-(5+0,7y)-(0,9-0,1x)+(x-0,1)=0,3x-5-0,7y-0,9+0,1x+x-0,1=
=1,4x-0,7y-6
h)0,5a+(5-0,8b+2a)-(-b+1)=0,5a+5-0,8b+2a+b-1=2,5a+0,2b+4
i)3/4-(1/4x+1/2)=3/4-1/4x-1/2=1/4-1/4x
j)1/3x+1/9y+(2/3y-4/9x-2/7)=1/3x+1/9y+2/3y-4/9x-2/7=
=3/9x-4/9x+1/9y+6/9y-2/7=-1/9x+7/9y-2/7
2010-03-09T16:06:20+01:00
A)
3b+(b+1)=
3b + b + 1 =
4b + 1

b)
5a-(a+1)=
5a - a - 1 =
4a - 1

c)
2x-(3-5-x)=
2x - (-2 - x) =
2x + 2 + x =
3x + 2

d)
2a+(3a-2b)+(a+b)=
2a + 3a - 2b + a + b =
6a - b

e)
5a-(2-x)+b-2x+5=
5a - 2 + x + b - 2x + 5 =
5a - x + b + 3

f)
7k-(m-2n+k)-(5k-3)+(2k-1)=
7k-m+2n-k-5k+3+2k-1 =
3k-m+2n+2

g)
0,3x-(5+0,7y)-(0,9-0,1x)+(x-0,1)=
0,3x- 5 - 0,7y - 0,9 + 0,1x +x - 0,1 =
1,4x -0,7y -6

h)
0,5a+(5-0,8b+2a)-(-b+1)=
0,5a + 5 - 0,8b + 2a + b - 1 =
2,5a - 0,2b + 4

i)
3/4-(1/4x+1/2)=
0,75 - ( 0,25x + 0,5)=
0,75 - 0,25x - 0,5 =
0,25 - 0,25x

j)
1/3x+1/9y+(2/3y-4/9x-2/7)=
⅓x + ¹/₉y + ⅔y - ⁴/₉x - ²/₇ =
³/₉x + ¹/₉y + ⁶/₉y - ⁴/₉x - ²/₇ =
-¹/₉x + ⁷/₉y - ²/₇

POZDRAWIAM :)
1 5 1